Training programmes for practitioners in sexual health promotion: an integrative literature review of evaluations. Issue 1 (2nd January 2022) - Begley, Thelma; Daly, Louise; Downes, Carmel; De Vries, Jan; Sharek, Danika; Higgins, Agnes
ABSTRACT: This paper reports on findings from an integrative literature review of evaluation studies undertaken into sexual health promotion preparation programmes aimed at professionals with a sexual health promotion remit. Using a pre-defined search strategy, inclusion criteria and PRISMA guidelines, databases were systematically searched. Studies were screened and those included were quality assessed. Twenty-seven relevant studies were identified. Thematic analysis showed programmes were diverse in terms of how they had been developed, the content included, approaches to evaluation and outcomes identified. Evaluations showed participation in a training programme encouraged participants to feel more comfortable and confident to discuss sexual health within their role and more likely to introduce sexual health into client discussions. The types of programmes and evaluation approaches were diverse making direct comparison between them challenging. There should be agreed core outcome impact measures for sexual health education programmes in the areas of knowledge, comfort, skills and changes to practice, to allow for more direct comparison in future evaluation studies.